2010
DOI: 10.1007/s13105-010-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

Testicular oxidative damage and role of combined antioxidant supplementation in experimental diabetic rats

Abstract: The present study was designated to assess oxidative damage and its effect on germ cell apoptosis in testes of streptozotocin (STZ)-induced diabetic rats. The role of antioxidant supplementation with a mixture of vitamins E and C and alpha lipoic acid for protection against such damage was also evaluated. Forty-five adult male rats were randomly divided into three groups: group I, control, non-diabetic rats; group II, STZ-induced, untreated diabetic rats; group III, STZ-induced diabetic rats supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 37 publications
(33 reference statements)
7
39
1
Order By: Relevance
“…These observations led us to assume that a potent antioxidant is crucial in reducing the damage caused by oxidative stress. Some experimental, epidemiological and clinical studies also emphasize that antioxidants might be helpful for treating diabetes and its complication [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These observations led us to assume that a potent antioxidant is crucial in reducing the damage caused by oxidative stress. Some experimental, epidemiological and clinical studies also emphasize that antioxidants might be helpful for treating diabetes and its complication [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[192021] Several studies have shown that antioxidant treatment improves glycemic index, reduces diabetic complications, and protects components from oxidative damage. [2223]…”
Section: Introductionmentioning
confidence: 99%
“…Suppressed testosterone secretion as a result of diminished Leydig cell function (Pitteloud et al, 2005) has been reported in T2DM. Decreased serum concentrations of reproductive hormones (testosterone, FSH and LH) have also been reported in DM animal models induced by STZ (Mohasseb et al, 2011;Kanter et al, 2013), alloxan (Hafez, 2010;Ghlissi et al, 2012) and nicotinamide+STZ (Ahangarpour et al, 2015), and in BB rats (Cameron et al, 1990). These studies show a unified pattern of events irrespective of the diabetic model used.…”
Section: Pre-testicular Effects Of Diabetes Mellitus (Hypothalamicpitmentioning
confidence: 78%
“…Studies with both T1 and T2 diabetic animal models have shown significant decreases in antioxidant enzymes and a significant increase in lipid peroxidation in the testis. Reports from studies using STZ-induced T1DM rats have shown significant decreases in testicular superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities, and a significant increase in malondialdehyde (MDA) level (Mohasseb et al, 2011;Kanter et al, 2013).…”
Section: Testicular Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation